Robotics: Science and Systems XI 2015
DOI: 10.15607/rss.2015.xi.042
|View full text |Cite
|
Sign up to set email alerts
|

Online Localization of Radio-Tagged Wildlife with an Autonomous Aerial Robot System

Abstract: Abstract-The application of autonomous robots to efficiently locate small wildlife species has the potential to provide significant ecological insights not previously possible using traditional landbased survey techniques, and a basis for improved conservation policy and management. We present an approach for autonomously localizing radio-tagged wildlife using a small aerial robot. We present a novel two-point phased array antenna system that yields unambiguous bearing measurements and an associated uncertaint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
112
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(116 citation statements)
references
References 28 publications
3
112
1
Order By: Relevance
“…Other efforts have focused specifically on the case of tracking radio-tagged fish Leonardo et al 2013;Jensen et al 2014), including mathematical modeling, computer simulations, the design of a UAS-borne telemetry tracking payload and live flight tests (without real animals). Cliff et al (2015) most recently demonstrated real-time autonomous localization of radio-tagged noisy miners (Manorina melanocephala) at short range by a multirotor UAS. It should be noted that beyond technological challenges, a potential major impediment to UAS-based wildlife telemetry tracking is the regulation of airspace: presumably the technique would routinely require flying the UAS beyond visual line of sight (BVLOS) of ground operators, a practice that is currently heavily regulated in most developed countries.…”
Section: Uas For Autonomous Wildlife Telemetry Trackingmentioning
confidence: 99%
“…Other efforts have focused specifically on the case of tracking radio-tagged fish Leonardo et al 2013;Jensen et al 2014), including mathematical modeling, computer simulations, the design of a UAS-borne telemetry tracking payload and live flight tests (without real animals). Cliff et al (2015) most recently demonstrated real-time autonomous localization of radio-tagged noisy miners (Manorina melanocephala) at short range by a multirotor UAS. It should be noted that beyond technological challenges, a potential major impediment to UAS-based wildlife telemetry tracking is the regulation of airspace: presumably the technique would routinely require flying the UAS beyond visual line of sight (BVLOS) of ground operators, a practice that is currently heavily regulated in most developed countries.…”
Section: Uas For Autonomous Wildlife Telemetry Trackingmentioning
confidence: 99%
“…However, these studies did not experiment on live animals (dos Santos et al 2014;Cliff et al 2015), while our study presents similar results but with live birds flying free in their natural environment. Furthermore, our system (Motus technology and a small UAV) is simpler to use and more affordable than that of Cliff et al (2015), who used a commercial UAV platform coupled with a recording ground station. While dos Santos et al (2014) did use a similar system to ours, our results on live birds in nature confirmed their experimental findings collected under controlled conditions.…”
Section: Resultsmentioning
confidence: 55%
“…This change has started happening, at a small but increasing scale (Pimm et al, 2015, Marvin et al, 2016Snaddon et al, 2013). More and more, conservation researchers and practitioners are not content with simply looking for existing technological tools, but rather actively seek to design and produce new and innovative solutions to tackle specific needs, from relatively simple yet useful devices (e.g., smart nest box monitoring system, Zárybnická, Kubizňák, Šindelář, & Hlaváč, 2016; low-cost open-source programmable acoustic logger, Hill et al, 2018) to complex systems (e.g., large-scale realtime monitoring of elephant movement behaviour, Wall, Wittemyer, Klinkenberg, & Douglas-Hamilton, 2014; Unmanned Aerial System to automatically locate radio-tagged wildlife, Cliff, Fitch, Sukkarieh, Saunders, & Heinsohn, 2015). Such solutions usually involve interdisciplinary teams of conservationists/ecologists and engineers/computer scientists.…”
Section: Facilitating Small-scale Innovationmentioning
confidence: 99%